Planning for and responding to pandemic influenza emergencies: it’s time to listen to, prioritize and privilege Aboriginal perspectives - Crooks, Kristy; Massey, Peter; Taylor, Kylie; Miller, Adrian; Campbell, Sandra; Andrews, Ross (Western Pacific Surveillance and Response, 2018)
Aboriginal and Torres Strait Islander peoples continue to experience disproportionately higher rates of mortality and hospitalisation for many infectious diseases.  In the past, infectious disease emergency planning and response failed to include Aboriginal people.  Aboriginal worldviews and Aboriginal voices must now be valued, and incorporated into health policy and practice.